Maternal and paternal depressive symptoms and parental vocalisation behaviours in infancy: findings from UK-based birth cohort - Campbell, Amy; Lewis, Gemma; Costantini, Ilaria; Cordero, Miguel; Skinner, Andy; Dermott, Esther; Miller, Tina; Kennedy, Mari-Rose; Culpin, Iryna (Frontiers in Child and Adolescent Psychiatry, 2023)
Background: Both maternal and paternal postnatal depression (PND) are associated with increased risk of less optimal offspring developmental outcomes. Early exposure to differences in maternal and paternal vocalisation behaviours associated with maternal and paternal PND may be important in this relationship. However, little research has captured vocalisation patterns at home without researchers present. Objectives: This study sought to examine the associations between maternal and paternal PND and various aspects of parental vocalisation behaviours. Methods: Mothers (n=104) and fathers (n=34) of six-month-s old infants from the Avon Longitudinal Study of Parents and Children Generation-2 (ALSPAC-G2) provided video footage of mother- and father-infant interactions filmed at home using the head-worn video cameras (headcams) without the need for researchers to be present. Twenty-five mother-infant and father-infant interactions were coded on multiple aspects of parental and infant vocalisation behaviours using the micro-behavioural observational coding system. Parental (PND) was measured using the Edinburgh Postnatal Depression Scale (EPDS; total score). Results: Frequencies and duration of vocalisation behaviours were similar in mothers and fathers. H, however, there was an indication that fathers demonstrated higher frequency and duration of commands, exclamations and ironic/sarcastic tone, and criticisms compared to mothers, while mothers engaged in more teaching compared to fathers. Linear regression models indicated that maternal and paternal PND were not associated with the majority of vocalisation behaviours., Hhowever, there were some specific patterns observed, mostly related to the emotional tone of the vocalisations. Higher levels of maternal PND were associated with lower frequency of speech in a neutral tone, frequency and duration of use of humour, and increased duration of speech in a positive tone. Higher levels of paternal PND were associated with higher mean duration of speech, infant-directed speech, higher frequency and duration of laughing, and increased duration of speech using questions and encouragement. Conclusion: These findings extend existing research by investigating the associations between maternal and paternal PND and a wide range of vocalisation behaviours captured and coded using innovative methods and in a more ecologically valid way than previous studies.